A139: Body Mass Index and Height Change Over Time in Childhood‐Onset Systemic Lupus Erythematosus Cohort. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Harris, Julia G.; Maletta, Kristyn I.; Kuhn, Evelyn M.; Olson, Judyann C.
Abstract : Background/Purpose: Systemic lupus erythematosus (SLE) can lead to significant morbidity and mortality related to coronary artery disease. Obesity is an additional risk factor for cardiovascular disease that appears to be more prevalent in this population. Obesity in SLE has been linked to decreased health‐related quality of life, functional limitations, pain, fatigue, diabetes mellitus, and increased malignancies. In addition, growth retardation is an important aspect to consider in a child or adolescent that is exposed to corticosteroids. Growth failure has been a proposed addition to the Systemic Lupus International Collaborating Clinics/American College of Rheumatology Damage Index (SDI) to modify this validated scale for childhood‐onset SLE (cSLE). There is limited data discussing change in growth parameters over time in cSLE patients, which our study sought to do. Methods: A retrospective chart review was performed on patients diagnosed with SLE prior to age 18 who were followed in the Children's Hospital of Wisconsin Rheumatology Clinic for at least one year between January 1999 and August 2012. Weight and height were collected two times per year. Body mass index (BMI; kg/m 2 ) and percentiles of measurements for age were calculated based on sex‐specific growth references from the Centers for Disease Control and Prevention for patients 2 to 20 years old. Additional information collected included age of diagnosis, medication use, presence of lupus nephritis, and items of disease damage based on the SDI. Results: Analysis was performed on 75 patients with mean disease duration of 4.55 years. There were 685 growth for age percentile values recorded. Mean BMI percentage per age at diagnosis was 64.81 compared to 76.31 at the 610 follow‐up visits, which was statistically significant (p < 0.001). At diagnosis, 33.3% of patients were overweight (≥85–95% BMI for age), obese (≥95–99% BMI for age), or severely obese (≥99% BMI for age) versus 49.3% at last available follow‐up visit. Sixty‐eight percent of patients had at least one BMI measurement out of the normal range. Mean percent height for age at diagnosis was 64.21 versus 46.58 at follow‐up visits (p < 0.001). Eight of the seventy‐five patients had growth percentiles <5% at last follow‐up visit. Conclusion: A majority of our cSLE population was overweight or obese during at least one time period. In addition, BMI statistically increased from diagnosis to follow‐up visits. Growth failure was present in greater than 10% of the population, and percent height for age statistically decreased after diagnosis as well. Interventions related to healthy living habits and medication adjustments should be made to address these important growth issues that can have long‐standing complications.